Dis/orientating the Early Childhood Sensorium: A Palate Making Menu for Public Pedagogy - Berry, Alex; Pollitt, Jo; Nelson, Narda; Hodgins, B. Denise; Wintoneak, Vanessa (Journal of Childhood Studies, 2022)
This paper shares a multilayered retrospective story of an international exhibit curated for the Climate Action Childhood Network Colloquium as part of a commitment among exhibit curators to reveal the complexities of unpalatable climate futures. In the format of a tasting menu, we offer a sampling of the exhibit installations as a menu of potential alterpolitics in the making. Facing intensifying inequitable climate presents and futures, our intention is that this invitation might create openings for the intersection of local and global concerns. We gesture toward collective but tentative responses for thinking climate action pedagogies through the metaphor of a troubling meal.